Inggris - Mely Yani; Amprasto; Rini Solihat (Jurnal Penelitian Pendidikan IPA, 2023)
This was a descriptive study aims to analyze how the research skills of Junior High School Students, especially in plant propagation material. The research subjects consisted of 36 IX grade Junior High School students. The research skills measured consisted of five indicators, namely observing, questioning, planning, analyzing, and communicating. Data were obtained used a valid and reliable test instrument in the form of 17 essay questions. The data were recapitulated and analyzed by a simple statistical analysis. The results showed that students' average research skills score were in a low category. Most students have very low research skills. Questioning, analyzing, and communicating indicator were low. The highest average score was observing indicator in average category. The lowest average score was planning indicator in very low category. This showed that there is a need to increase the research skills of junior high school students by involving them regularly in the research process.